Barrier membranes for tissue regeneration in dentistry. Issue 1 (1st January 2021) - Sasaki, Jun-Ichi; Abe, Gabriela L.; Li, Aonan; Thongthai, Pasiree; Tsuboi, Ririko; Kohno, Tomoki; Imazato, Satoshi
Abstract: Background: In dentistry, barrier membranes are used for guided tissue regeneration (GTR) and guided bone regeneration (GBR). Various membranes are commercially available and extensive research and development of novel membranes have been conducted. In general, membranes are required to provide barrier function, biosafety, biocompatibility and appropriate mechanical properties. In addition, membranes are expected to be bioactive to promote tissue regeneration. Objectives: This review aims to organize the fundamental characteristics of the barrier membranes that are available and studied for dentistry, based on their components. Results: The principal components of barrier membranes are divided into nonbiodegradable and biodegradable materials. Nonbiodegradable membranes are manufactured from synthetic polymers, metals or composites of these materials. The first reported barrier membrane was made from expanded polytetrafluoroethylene (e-PTFE). Titanium has also been applied for dental regenerative therapy and shows favorable barrier function. Biodegradable membranes are mainly made from natural and synthetic polymers. Collagens are popular materials that are processed for clinical use by cross-linking. Aliphatic polyesters and their copolymers have been relatively recently introduced into GTR and GBR treatments. In addition, to improve the tissue regenerative function and mechanical strength of biodegradable membranes, inorganic materials such as calcium phosphate and bioactive glass have been incorporated at the research stage. Conclusions: Currently, there are still insufficient guidelines for barrier membrane choice in GTR and GBR, therefore dentists are required to understand the characteristics of barrier membranes.